PEMBUATAN MEMBRAN POLIMER BERBASIS MAKROFILTER MENGGUNAKAN ALPA SELULOSA DENGAN PENAMBAHAN ZnO DAN SILIKA FIBER - Anggi Wahyuningsi; Indah Agus Setiorini; Rama Gusti (LPSDI Bina Patria, 2025)
Membrane is defined as a selective and semipermeable thin layer lying between two phases; the feed phase and the permeate phase. The selective properties of this membrane can be used in separation process. In this research, the membrane was made using alpa cellulose, silica fiber with addition of ZnO which was printed using the phase inversion method. This research carried out characteristic testing to find out SEM, FTIR and bulk density test results. The SEM test results we obtained from the test results were depth filters because they had fibers that were not woven and stacked randomly in the matrix, visible on the surface that was rough, not smooth, and not dense due to the addition of silica fiber. From FTIR test results, the membrane we made contained more alkanes (C-H), alkalyne (C≡C), and alcohol (C-O) compounds with an average of 91% with strong intensity. This membrane had the highest bulk density value of 0.1566 gr/cm3 out of the membranes obtained using 0.14 gr alpa cellulose composition, and the lowest bulk density result obtained with 0.1 gr alpa cellulose composition was 0.1 gr/m3. High density had dense structures and smaller pores and therefore increasing selectivity.